Emerging organic contaminants in soil irrigated with effluent: electrochemical technology as a remediation strategy - Ferreira, Ana Rita (2022)
Financial support was provided by: 4KET4Reuse ( SOE1/P1/E0253 ) and CEMOWAS 2 ( SOE2/P5/F0505 ), co-financed by the European Regional Development Fund (FEDER). Fundação para a Ciência e a Tecnologia , I.P., Portugal, UIDB/04085/2020 (Research unit CENSE “Center for Environmental and Sustainability Research”). N. Couto Contract established under Individual Call to Scientific Employment Stimulus ( CEECIND/04210/2017 ). P. Guedes fellowship ( SFRH/BPD/114660/2016 ).